(untitled) (Indian Journal of Public Health Research & Development, 2021)
Omenn Syndrome is a rare combined immunodeficiency syndrome manifested mainly by generalised erythroderma, alopecia, loss of eyebrow and eye lashes, generalised oedema and metabolic disturbances. Poor prognosis is reported as it mimics the appearance of severe eczema and immunodeficiency and is under noticed as there is presence of circulating lymphocytes. Understanding the guidelines of prompt diagnosis will facilitate early treatment and improve prognosis.